2009
DOI: 10.1007/s11814-009-0245-0
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of H3PW12O40 catalyst in the direct preparation of dichloropropanol (DCP) from glycerol and hydrochloric acid gas

Abstract: Methods for regenerating H 3 PW 12 O 40 catalyst in the solvent-free direct preparation of dichloropropanol (DCP) from glycerol and hydrochloric acid gas were investigated. Regenerated H 3 PW 12 O 40 catalyst was then applied to the solvent-free direct preparation of DCP. In the solvent-free direct preparation of DCP, selectivity for DCP over H 3 PW 12 O 40 catalyst regenerated by method I (recovery of solid H 3 PW 12 O 40 catalyst by evaporating homogeneous liquidphase product solution) significantly decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The H 3 PW 12 O 40 catalysts were able to be regenerated by evaporating the solution after the reaction, followed by oxidative calcination and recrystallization. Such a regenerated H 3 PW 12 O 40 catalyst showed catalytic activity and a selectivity of dichlorohydrin similar to the fresh catalyst (394). It was found that water formed during the reaction had a negative effect on Downloaded by [Princeton University] at 04:47 17 September 2013 the formation of dichloropropanol.…”
Section: Catalytic Chlorination Of Glycerol To Dichloropropanolmentioning
confidence: 85%
“…The H 3 PW 12 O 40 catalysts were able to be regenerated by evaporating the solution after the reaction, followed by oxidative calcination and recrystallization. Such a regenerated H 3 PW 12 O 40 catalyst showed catalytic activity and a selectivity of dichlorohydrin similar to the fresh catalyst (394). It was found that water formed during the reaction had a negative effect on Downloaded by [Princeton University] at 04:47 17 September 2013 the formation of dichloropropanol.…”
Section: Catalytic Chlorination Of Glycerol To Dichloropropanolmentioning
confidence: 85%
“…Compared to Fe 3 O 4 @ZIF-8, the Fe 3 O 4 @ZIF-8@H 3 PW 12 O 40 not only retains the characteristic peak of Fe 3 O 4 @ZIF-8, but also contains the characteristic peak of POM: bands at 891, 980 and 1077 cm −1 can be assigned to W–O–W, WO and P–O in H 3 PW 12 O 40 . 41 However, the characteristic peaks of H 3 PW 12 O 40 show deviation, possibly due to the strong interaction between H 3 PW 12 O 40 and Fe 3 O 4 @ZIF-8, leading to the change of electron cloud density. 42 As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Oxygen at 6N was used as an oxidizing gas. The typical growth conditions of PbO, ZrO 2 and TiO 2 thin film are listed in Table 1; MOCVD details are available in the literature [14]. A multilayer structure of binary oxides was prepared as follows: first, an initial oxide layer of either PbO, ZrO 2 or TiO 2 was deposited.…”
Section: Methodsmentioning
confidence: 99%